Urgensi Implementasi Pendidikan Agama Islam terhadap Pembentukan Akhlak dan Sopan Santun Siswa di SMP Negeri 1 Sitiung Dharmasraya - Wensi, Edmily; M, Iswantir; Neli, Ana Fitri (Lembaga Yasin AlSys, 2023)
In this study, it discusses the Importance of Islamic Religious Education in the Formation of Morals and Manners of Students at SMP N 1 SITIUNG. The problem in this study is